PEMBERDAYAAN MASYARAKAT TANI KOTA DENPASAR MENUJU PERTANIAN RAMAH LINGKUNGAN MELALUI PELATIHAN PEMBUATAN PUPUK MINERAL PLUS - Lanya, Indayati; N. N., Subadiyasa; Kusmawati, Tatiek; Adi, I G. P.Ratna; Dibia, N.; Kusmiyarti, Tati Budi; Sardiana, K.; Wikarniti, N. M. (Buletin Udayana Mengabdi; Vol 12 No 1 (2013): Volume 12 No.1 – April 2013, 2013)
Environment issues and go green impacted to perception of political makers both in governmental and private sector. The organic farming was identical to decrease fertilizer application of chemical fertilizer. This issue should be researched whether chemical fertilizer destroyed environment or vice verse. Since 1998 research found and concluded that the opposite perception was due to the high dosage organic fertilizer. Dissemination of research found that mineral plus processing was conducted in Anggabaya Village. It was done by exercising farmer society with empowering technology. Raw material of mineral plus fertilizer process has been formulated by the team, and the targets were the farmers and farming family to improve their knowledge in processing fertilizer and applying it for farmer use. The training was conducted after presentation and discussion so the participant more understood the use of fertilizer and quality of fertilizer. The team as tutors in formulating mineral plus fertilizer and participated by most of participants (90%). The participants were very responsive in mineral plus formulating and most of them making formulate from the available material. The information from the participant that organic fertilizer yielded low production and farmers use quicklime in papaya garden which produced more sweetened fruits.